NCTzen Fandom Bandung Fanaticism on K-Pop Idol NCT - Nuha, Mohammad Nadwa Ulin; Wahyudin, Uud; Gemiharto, Ilham (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
The development of technology, the emergence of various K-Pop groups that began to bewitch the Indonesian people. One of them, a boy group made by SM Entertainment, namely NCT. The NCTzen phenomenon increasingly shows that the movement of the Korean entertainment industry is mushrooming in Indonesian society. This study aims to find out the motives, experiences, and meanings of fanaticism for NCTzen Bandung in liking NCT. Fanaticism comes from the meaning of being a fan, where